2000
DOI: 10.1023/a:1006379925343
|View full text |Cite
|
Sign up to set email alerts
|

Association between immunity and prognostic factors in early stage breast cancer patients before adjuvant treatment

Abstract: The association of NK cell counts and beta2-microglobulin or sIL-2r serum levels with prognostically favorable factors such as ER positive tumor and older age supports the assumption that the immune system plays a role in the course of early breast cancer. The exact nature of this role requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Klein et al (1991) proved the correlation between B2-M and clinical course of disease in 365 women with breast cancer. Also Sabbioni et al (2000) observed some impact of subjective burden in patients with early breast cancer on soluble immune measures, including B2-M and sIL-2R , determined serially during and after chemotherapy. Stefanovic et al (1999) have observed the signiWcant decrease of the elevated pretreatment serum B2-M values following resection of the tumour in patients with urothelial carcinoma.…”
Section: B2-mmentioning
confidence: 92%
“…Klein et al (1991) proved the correlation between B2-M and clinical course of disease in 365 women with breast cancer. Also Sabbioni et al (2000) observed some impact of subjective burden in patients with early breast cancer on soluble immune measures, including B2-M and sIL-2R , determined serially during and after chemotherapy. Stefanovic et al (1999) have observed the signiWcant decrease of the elevated pretreatment serum B2-M values following resection of the tumour in patients with urothelial carcinoma.…”
Section: B2-mmentioning
confidence: 92%
“…In contrast, solid malignancies usually are not associated with elevations in serum sCD25 unless the disease has disseminated [48][49][50][51]. Elevated sCD25 levels in the ascites of ovarian cancer patients and in the serum of breast cancer patients correlated with a low frequency of TILs, suggesting that sCD25 could inhibit antitumor immunosurveillance [52]. sCD25 suppresses IL-2-induced surface CD25 expression and T cell responses in vitro [30,31,[53][54][55].…”
Section: -Test) (F)mentioning
confidence: 99%
“…Thus, we consider that IL-19 produced by breast cancer cells promotes tumor progression not only by its autocrine effect but also by providing a microenvironment for tumor growth and metastasis. Furthermore, cytokines are mediators of the effector response from innate and acquired cellular immunities (49,50); they are probably involved in the mechanism for tumor cell evasion in the immunosurveillance system. This might also be one of the mechanisms by which overexpression of IL-19 in breast cancer cells promoted tumor growth and metastasis in vivo.…”
Section: Discussionmentioning
confidence: 99%